Strategi Kampanye Yayasan Pejuang Tangguh Dalam Membangun Citra Organisasi Melalui Program “Dengan TPT Cegah TBC” - Putri Marshada Lestari; Syifa Astasia Utari (GLOBAL SCIENTS PUBLISHER, 2026)
A campaign is a public relations activity that can be a strategy in building a positive organizational image. This is because the campaign allows the organization to convey messages according to public needs, including the issue of Tuberculosis which is currently a challenge in Indonesia due to a lack of education. Therefore, the Pejuang Tangguh Foundation (PETA) runs the